Search 81,698 tutors
FIND TUTORS
Ask a question
0 0

quadratic formula

Tutors, please sign in to answer this question.

1 Answer

use quadratic formula   -6+or-√(36+4*1*27) = (-6 ± √144)/2 = (-6±12)/2 = -9,+3
 
 
 
3X2= 39    X2=13   x=±√13
 
move the -27 to the other  side of the problem
now we have X2 + 6 x = 27
Complete the square on the left side   6/2=32 = 9
 
add 9 to both sides of the problem
 
X2 + 6x +9 = 27 + 9 = 36
 
 
(X + 3 )2  = 36
 
Take the square root of both sides
 
X+3 = ± 6
 
X= -3-6 = -9   and  -3+6 = +3

Comments